Presentation of Malaria Epidemics Using Multiple Optimal Controls - Abid Ali Lashari; Shaban Aly; Khalid Hattaf; Gul Zaman; Il Hyo Jung; Xue-Zhi Li (Journal of Applied Mathematics)
An existing model is extended to assess the impact of some antimalaria control measures, by re-formulating the model as an optimal control problem. This paper investigates the fundamental role of three type of controls, personal protection, treatment, and mosquito reduction strategies in controlling the malaria. We work in the nonlinear optimal control framework. The existence and the uniqueness results of the solution are discussed. A characterization of the optimal control via adjoint variables is established. The optimality system is solved numerically by a competitive Gauss-Seidel-like implicit difference method. Finally, numerical simulations of the optimal control problem, using a set of reasonable parameter values, are carried out to investigate the effectiveness of the proposed control measures.